HBsAg kinetics during and after nucleos(t)ide analogues described by mathematical modeling. (March 2023) - Colombatto, P.; Civitano, L.; Coco, B.; Cavallone, D.; Oliveri, F.; Ricco, G.; Santucci, M.; Damone, F.; Romagnoli, V.; Salvati, A.; Surace, L.; Bleve, P.; et al.
Abstract : Introduction: HBsAg clearance (functional cure) is the optimal endpoint of chronic hepatitis B treatment. Nucleo(s)tide analogues (NAs) have a limited impact on HBsAg decline, however achieving low HBsAg serum levels correlates with loss after discontinuation. Aim: To investigate mechanisms of HBsAg decline during NAs. Materials and Methods: We set up a mathematical model describing: 1) dynamics of replication-competent hepatocytes (cccDNA>1 copy/cell) producing HBsAg by either cccDNA or integrated DNA (intDNA); 2) cccDNA turnover; 3) dynamics of non-replication-competent hepatocytes which lost cccDNA by cell division, but still produce HBsAg by intDNA. Baseline I0-cccDNA and their immune-mediated clearance rate were computed by ALT decline upon NAs block of HBV replication; cccDNA lifetime by fitting ALT, HBV-DNA and HBsAg; HBsAg production rate constants (from I0-cccDNA and I0-intDNA ), I0-intDNA and their lifetime by fitting HBsAg. We applied the model in 29 HBeAg-neg and 2 HBeAg-pos patients, median age 56.1(30-76.6) years, 21(65.6%) males, 17(54.8%) with cirrhosis. Median NAs treatment was 123.1(41.2-260.1) months. HBV-DNA (COBAS-TaqMan, Roche) and HBsAg (Architect, Abbott) were tested every six months. Results: HBsAg during NAs showed 3 different patterns: steady (3;9.6%), monophasic (18;58.1%) and multiphasic (10;32.3%) decline. Mean baseline ALT and HBsAg were lower in monophasic (121±95vs666±565 U/L, p=0.0004 and 4, 421.9±2, 876, 2vs18, 846.8±22, 861.3 IU/mL, p=0.0272). Overall, 6(19.4%) lost HBsAg: 5(17.2%) HBeAg-neg (4 during, 1 after NAs) and 1 (50%) HBeAg-pos (after discontinuation-retreatment). Patients who lost HBsAg on-therapy had multiphasic declines, successfully described by the model (Figure). Monophasic patients had lower I0-cccDNA (22.0%±15.4%vs54.8%±27.3%, p=0.0159) and HBsAg production by cccDNA (1.7%±2.3vs53.3%±27.3%, p<0.0001). Lifetime of IintDNA was longer in monophasic (3, 938±2, 681 vs 1, 340±875 days, p=0.0065), cccDNA lifetime was similar (52±52vs31±14 days, p=0.2288). Conclusions: Mathematical modeling showed that faster HBsAg decline after NAs was associated with higher disease activity and prevalent HBsAg production from cccDNA, with lifetime shorter of intDNA. HBsAg loss was characterized by multiphasic declines.